2009
DOI: 10.1136/emj.2008.061192
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study of tracheal intubation in an emergency department in a 2300-bed hospital of a developing country in a one-year period

Abstract: At this institution, the majority of ED intubations were performed by residents and no drug was used. In this ED patients were intubated with a high success rate and a low rate of serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
6
15
0
Order By: Relevance
“…The first priority for managing an acutely unstable patient is securing the airway. Approximately 0.5–1% of emergency department (ED) patients require intubation for various conditions, such as respiratory failure, cardiac arrest, and altered mental status . Emergency airway management in the ED is often challenging for the emergency physician because multiple ED‐specific factors, for example, vomiting, facial/neck trauma, immobilized cervical spine, and chest compression for resuscitation, contribute to intubation success and failure.…”
Section: Introductionmentioning
confidence: 99%
“…The first priority for managing an acutely unstable patient is securing the airway. Approximately 0.5–1% of emergency department (ED) patients require intubation for various conditions, such as respiratory failure, cardiac arrest, and altered mental status . Emergency airway management in the ED is often challenging for the emergency physician because multiple ED‐specific factors, for example, vomiting, facial/neck trauma, immobilized cervical spine, and chest compression for resuscitation, contribute to intubation success and failure.…”
Section: Introductionmentioning
confidence: 99%
“…Airway management is a fundamental aspect of many of the major resuscitations that take place in our EDs and a skill that emergency physicians (EPs) should deliver in a safe and timely manner. A number of observational studies have been published describing how this practice is performed in EDs across the world either at a single or multicentre level. Following the publication of data on ED intubation from our institution, it was decided to implement a bundle of changes to our practice in order to improve patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…The 24 articles chosen for final review are listed in Table 2 below and the references section 11–34 . An annotated bibliography including final summary and critical analysis of each article can be found in Data Supplement S1 (available as supporting information in the online version of this paper).…”
Section: Resultsmentioning
confidence: 99%
“…Another crucial topic is development of EM skills among already practicing clinicians. Wongyingsinn et al 34 demonstrated progress on this front by studying emergency department intubations by EM residents and EM staff physicians at a tertiary academic medical center in Thailand, finding success rates comparable to those in developed countries, despite areas for improvement including low rates of utilization of neuromuscular blockade, high rates of soft tissue injury, and no use of awake fiberoptic techniques.…”
Section: Discussionmentioning
confidence: 99%